Au-catalyzed InP nanowires: The influence of growth temperature and V/III ratio - Paiman, S; Gao, Q; Joyce, H; Tan, H; Jagadish, C; Kim, Y; Guo, Y; Zou, J (2010)
Growth of Au-catalyzed InP nanowires (NWs) by metalorganic chemical vapor deposition (MOCVD) has been studied in the temperature range of 400-510 °C and V/III ratio of 44-700. We demonstrate that minimal tapering of InP NWs can be achieved at 400 °C and V/III ratio of 350. Zinc-blende (ZB) or wurtzite (WZ) NWs is obtained depending on the growth conditions. 4K microphotoluminescence (μ-PL) studies show that emission energy is blue-shifted as growth temperature increases. By changing these growth parameters, one can tune the emission wavelength of InP NWs which is attractive for applications in developing novel optoelectronic devices. © 2010 IEEE.